Service Effectiveness and Ease of Ordering on Customer Experience - Angelia Widhy; Putri Esthi Palupi; Juliana Juliana; Amelda Pramezwary; Jimmy Muller Hasoloan Situmorang (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The modern restaurant industry is characterized not only by the successful delivery of quality food, but also by the ability to provide effective service. In order to increase customer experience, productive measures are needed to increase effectiveness. The purpose of this. study is to analyze the effectiveness of service and ease of ordering in order to improve the customer experience at Hai Di Lao Restaurant so that customer have intensity to come back again. This research uses quantitative methods using of 160 respondents of restaurant customers with purposive sampling techniques where the example criteria are customers who have visited the Restaurant at least 1 time a month. The results of this study prove that the higher service activities by the restaurant, the higher customers experience so that it can be implications for the intensity of customers returning to the restaurant. In future research, it is hoped that future research can consider using a larger sample, where a larger sample is more likely to generalize the findings. Businesses should invest in training programs to improve service effectiveness, ensuring that employees have the skills and knowledge necessary to deliver consistently high-quality service